Antinociceptive, anti-inflammatory and gastroprotective effects of a hydroalcoholic extract from the leaves of Eugenia punicifolia (Kunth) DC. in rodents - Basting, Rosanna T. [UNESP]; Nishijima, Catarine M. [UNESP]; Lopes, Juliana A. [UNESP]; Santos, Raquel C. [UNESP]; Perico, Larissa Lucena [UNESP]; Laufer, Stefan; Bauer, Silke; Costa, Miriam F. [UNESP]; Santos, Lourdes C. [UNESP]; Rocha, Lucia R. M. [UNESP]; Vilegas, Wagner [UNESP]; Santos, Adair R. S.; et al. (Elsevier B.V., 2014)
Ethnopharmacological relevance: An ethnopharmacological survey indicated that leaves from Eugenia punicifolia (Kunth) DC. (Myrtaceae) are popularly used as a natural therapeutic agent to treat pain and inflammation. Aim of the study: The overall objective of the present study was to evaluate the antinociceptive, antiinflammatory and gastroprotective activities of a hydroalcoholic extract of leaves from Eugenia punicifolia (HEEP) in rodents. Material and methods: The antinociceptive effects of HEEP were evaluated in mice after oral administration in chemical (formalin and glutamate) and thermal (hot-plate) tests. We evaluated the involvement of the glutamatergic, opioidergic and nitrergic pathways in the antinociception of HEEP and the effect of HEEP on the inhibition of p38α MAPK. The anti-inflammatory effect of HEEP was evaluated in mice and rats using xyleneinduced ear edema and carrageenan-induced paw edema, respectively. Furthermore, the gastroprotective effect of HEEP was evaluated in rats with acute gastric lesions induced by ethanol or indomethacin. Finally, we performed a phytochemical analysis of HEEP. Results: The oral administration of HEEP (125, 250 and 500 mg/kg, p.o.) significantly inhibited the neurogenic and inflammatory phases of formalin-induced licking, and HEEP (250 mg/kg, p.o.) also significantly inhibited the nociception caused by glutamate. The antinociceptive effects of HEEP were significantly reversed by Larginine (500 mg/kg, i.p.) but not by naloxone (1 mg/kg, i.p.) in the formalin test. HEEP did not affect animal motor performance in the rotarod model. In addition, HEEP also increased the paw withdraw latency in the hot-plate test. HEEP significantly inhibited ear edema induced by xylene (64%) and paw edema induced by carrageenan (50%) compared to the control group. Furthermore, HEEP (3–30 mg/mL) also inhibited the phosphorylation of p38α MAPK by approximately 90%. In addition, HEEP (125, 250 and 500 mg/kg, p.o.) protected the rats against ethanol (88.4–99.8%) and indomethacin (53–72.3%) and increased the mucus levels of the gastric mucosa without producing an antisecretory effect. The phytochemical profile of HEEP obtained using HPLC-PDA showed secondary metabolites already reported for the genus, mostly flavonoids, gallotannins and proanthocyanidins. Conclusions: These data show for the first time that HEEP has significant antinociceptive and antiinflammatory effects, which appear to be related to the inhibition of the glutamatergic system, the synthesis of nitric oxide and the inhibition of the phosphorylation of p38α MAPK. HEEP also has interesting gastroprotective effects related to the maintenance of protective factors, such as mucus production. These results support the use of Eugenia punicifolia in popular medicine and demonstrate that this plant has therapeutic potential for the development of phytomedicines with antinociceptive, anti-inflammatory and gastroprotective properties.
Keywords: Eugenia punicifolia; Myrtaceae; Antinociceptive; Anti-inflammatory; Gastroprotective; p38 alpha MAPK